2014
DOI: 10.1097/scs.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Meningitis and Frontal Encephalocele as Delayed Complications of Craniofacial Trauma

Abstract: Frontal sinus back table fractures are seen rarely; also, typical presentation of frontal sinus encephalocele as a delayed complication of frontal sinus fracture is seen more rarely. We present a case of frontal encephalocele and recurrent meningitis as delayed complications of craniofacial trauma. Diagnosis, management, and treatment approaches of these complications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Previous reports have shown that an acute encephalocele significantly increase the mortality of patients with acute ASDH [ 9 ]. Almost every neurosurgeon will experience it.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that an acute encephalocele significantly increase the mortality of patients with acute ASDH [ 9 ]. Almost every neurosurgeon will experience it.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Previous reports have shown that an acute encephalocele will signi cantly increase the mortality of patients with acute ASDH. [9] Almost every neurosurgeon will experience it. The common causes include contralateral subdural or epidural haematomas, epidural haematomas in the con uence of sinus areas, acute traumatic cerebral infarctions, and acute diffuse brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In these cases, acute diffuse brain swelling is particularly dangerous, with a high mortality and a poor prognosis. [9] How to judge the risk of intraoperative acute diffuse brain swelling in patients with traumatic ASDH based on the preoperative clinical data and imaging data is a problem that our neurosurgeon is more concerned about because this information can help us more accurately determine the operation risks and give the patients' families more accurate advice.…”
Section: Discussionmentioning
confidence: 99%
“…can be performed with fat tissue, fibrin sealant, and dural substitute. 9,17 Otherwise, transcranial approaches like the traditional Chula technique are preferred in cases with large or ectopic mass, which need some skin removal or recidivist case with previous scar face, but it leaves an inconvenient scar on the patient's face. 6 Some authors described a modified Chula technique, made with no facial incision, using a bicoronal approach to the hernial sac, with correction of skull defect.…”
Section: Discussionmentioning
confidence: 99%